Strengthening the attitude of cooperation through diversity projects - Lukmana, Ardila Riski; Sukmaningsih, Juwita; Sukmayadi, Trisna (Universitas Ahmad Dahlan, 2023)
This research describes the students' cooperation attitude as one of the dimensions of the Pancasila student profile. This research aims to determine the strengthening of the attitude of cooperation through the Strengthening Pancasila Student Profile Project activities. The method used in this research is a qualitative approach with observation and documentation data collection techniques. The results of this research are project-based learning activities that can strengthen the attitude of cooperation, involving teachers and students starting from the planning, implementation, and evaluation stages, namely through the Strengthening Pancasila Student Profile Project activity with the theme